Dielectric studies of composite paper reinforced with polypyrrole coated pulp fibers from wasted egg holders. Issue 33 (20th May 2015) - Razaq, Aamir; Idrees, Muhammad; Malik, Adeel; Mushtaq, Nafeesa; Nadeem, Muhammad; Hussain, Irshad; Yar, Muhammad
ABSTRACT Development of thin, flexible, light‐weight, renewable, low‐cost, and environmentally friendly electrode materials are highly feasible in era of modern disposable electronic technology. This article presents the synthesis and dielectric studies of polypyrrole (PPy) coated pulp fibers, directly collected from wasted egg holder's tray. PPy coated pulp fibers converted into compact sheet for the development of potential renewable and low‐cost electrode materials. The morphology, chemical structure, and thermal stability of naked and PPy coated pulp fibril sheets were investigated by scanning electron microscopy (SEM), Fourier transform infrared (FTIR) and thermogravimetric analysis (TGA), respectively. PPy coated pulp fibers revealed better thermal stability and compactness of sheet morphology. Impedance measurements showed a high value of dielectric constant of 1.15 × 106 at 0.5 Hz and conductivity of 7.45 × 10−4 S/cm at room temperature for PPy coated pulp fibril sheet. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42422.